Pengaruh Suhu pada Pengeringan Tepung Kimpul (Xanthosoma sagittifolium) - Sulistiawati, Endah; Santosa, Imam; APS, Yunizar Rizka; Saka, Arya Aji (Universitas Ahmad Dahlan, 2015)
Taro flour can be used as an alternative for wheat. This study aims to determine the optimal conditions on the operation of the drying resulting in minimal water content, but did not damage the properties of the desired material. This research will be obtained the parameters that can be used to design a dryer with a larger scale. After the taro peeled, washed, chopped and soaked with a solution of salt. Samples inserted into a dryer equipped with a balance, so that it can be read sample weight at a certain time. The drying process is stopped until the weight remains. The process of making flour baked, steamed after soaking the taro, and then do the drying process as the raw flour. The variables studied were temperature drying. The result showed that higher drying temperatures will accelerate the achievement of equilibrium moisture content, which means the drying operation requires a shorter period of time. Lower values of equilibrium moisture content on 0,02 (g water / g dry matter) can be achieved at a temperature of 90 0C, with a time of 80 minutes.